Transverse spin transfer to Λ and Λ hyperons in polarized proton-proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2018)
The transverse spin transfer from polarized protons to Λ and Λ hyperons is expected to provide sensitivity to the transversity distribution of the nucleon and to the transversely polarized fragmentation functions. We report the first measurement of the transverse spin transfer to Λ and Λ along the polarization direction of the fragmenting quark, DTT, in transversely polarized proton-proton collisions at s=200 GeV with the STAR detector at RHIC. The data correspond to an integrated luminosity of 18 pb-1 and cover the pseudorapidity range |η|<1.2 and transverse momenta pT up to 8 GeV/c. The dependence on pT and η are presented. The DTT results are found to be comparable with a model prediction and are also consistent with zero within uncertainties. © 2018 authors. Published by the American Physical Society.
Keywords: dept.phy; peer-reviewed